Decision Support System for Selecting Outstanding Teachers Using the Simple Additive Weighting Method at SD Negeri 14 Sitiung: Sistem Pendukung Keputusan Pemilihan Guru Berprestasi Menggunakan Metode Simple Additive Weighting di SD Negeri 14 Sitiung - Siti Aminah (Perkumpulan Doktor Indonesia Maju (PDIM), 2022)
The process of selecting outstanding teachers must comply with predetermined criteria. To assist in the selection of someone who deserves to be an outstanding teacher, a decision support system is needed. One method that can be used for a decision support system is to use the SAW (Simple Addictive Weighted) method, which is to find the best alternative from several alternatives. Where is the best alternative based on predetermined criteria. This method was chosen because it is able to choose the best alternative, namely the best teacher based on the criteria entered, then look for the weight value of each attribute, after the process of looking for rankings to get the best alternative, namely the outstanding teacher.